A Comparative Analysis of Indonesia’s KPK and Hong Kong ICAC in Eradicating Corruption - Ridwan Arifin; Rodiyah Rodiyah; Fitria Puspita (Jambe Law Journal, 2019)
This article seeks to discusses anti-corruption policies in Indonesia and Hong Kong. This research arises from the phenomenon of corruption that has become widespread in Indonesia and seems to be a never-endingproblem that has caused great damage in all sectors of life. It's not only a matter of how much the state loss or corrupt modus operandi that is even more sophisticated and even makes Indonesia one of the highest-rankingcountries in corruption cases, but it is also a matter of law enforcement whihch is less smart in handling corruption cases themselves. On the other hand, reportedly having a different approach in combating corruption, Hong Kong is considered to have been successful in carrying out its duties. With comparative study, this article will elaborate various patterns of work conducted by anti-corruption institutions in Indonesia and Hong Kong, namely the Corruption Eradication Commission (KPK) and the Independent Commission Against Corruption (ICAC).